Embryogenesis of the heart muscle - Sedmera, David; McQuinn, Tim (Heart failure clinics, 2008)
This article concerns the development of myocardial architecture--crucial for contractile performance of the heart and its conduction system, essential for generation and coordinated spread of electrical activity. Topics discussed include molecular determination of cardiac phenotype (contractile and conducting), remodeling of ventricular wall architecture and its blood supply, and relation of trabecular compaction to noncompaction cardiomyopathy. Illustrated are the structure and function of the tubular heart, time course of trabecular compaction, and development of multilayered spiral systems of the compact layer.
Keywords: kardiomyocyty; kontrakce myokardu; Heart; Myocardial Contraction; Ventricular Function; myokard; Embryonic Development; srdce - funkce komor; Humans; Myocardium; Myocytes, Cardiac; převodní systém srdeční; lidé; remodelace komor; Heart Conduction System; Ventricular Remodeling; embryonální vývoj; srdce